1985
DOI: 10.1152/jn.1985.54.2.261
|View full text |Cite
|
Sign up to set email alerts
|

Activation of dorsal horn cells by ventral root stimulation in the cat

Abstract: Responses of dorsal horn cells to ventral root stimulation were determined for the L7 and S1 levels of the spinal cord of 14 anesthetized cats. Forty-six dorsal horn cells were found that were excited by stimulation of the distal stump of the cut ventral root. For maximum excitation it was necessary to use a train of stimuli. For the 34 dorsal horn cells whose peripheral receptive-field properties could be characterized, 14 were wide dynamic range cells and 19 were high-threshold cells. The other cell responde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1986
1986
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Furthermore, the reflex response was caused by muscle contraction per se and not by direct electrical stimulation of afferents in the L 7 and S, ventral roots because the current intensity applied to the ventral roots in our experiments (i.e., 2.5 times motor threshold) was far too low to stimulate ventral root afferents 12 and to fire the dorsal horn cells that receive synaptic input from these afferents. 13 Chung et al 12 have demonstrated that the minimum current intensity needed to elicit reflex autonomic responses from electrical stimulation of ventral roots in paralyzed cats is 200 times motor threshold, a level of stimulation that is 80 times greater than that which we used to elicit muscle contraction.…”
Section: Discussionmentioning
confidence: 86%
“…Furthermore, the reflex response was caused by muscle contraction per se and not by direct electrical stimulation of afferents in the L 7 and S, ventral roots because the current intensity applied to the ventral roots in our experiments (i.e., 2.5 times motor threshold) was far too low to stimulate ventral root afferents 12 and to fire the dorsal horn cells that receive synaptic input from these afferents. 13 Chung et al 12 have demonstrated that the minimum current intensity needed to elicit reflex autonomic responses from electrical stimulation of ventral roots in paralyzed cats is 200 times motor threshold, a level of stimulation that is 80 times greater than that which we used to elicit muscle contraction.…”
Section: Discussionmentioning
confidence: 86%
“…This includes branches or loops of dorsal root afferents and pial afferents. Activation of this fibre group could elicit the phenomenon of recurrent sensitivity (Frykholm et al 1953;Chung et al 1985Chung et al , 1986. The results of the present study indicate that they are a small minority of the ventral root afferents and their relative contribution are discussed below.…”
Section: Some Ventral Root Afferents Do Enter the Spinal Cordmentioning
confidence: 52%
“…It is unclear whether the same applies for thin myelinated afferent fibres which are also present in the ventral root (see Results; Coggeshall et al 1974;Clifton et al 1976;Floyd et al 1976). On one hand, physiological studies have repeatedly failed to elicit pseudoaffective responses or to activate secondary spinal interneurones by stimulation of the central stump of the cut ventral root (Chung et al 1985(Chung et al , 1986. This shows that very few afferents enter the spinal cord through the ventral root or that these afferents do not have a prominent central effect.…”
Section: Quantitative Analysis Filaments Recorded From Intact Ventramentioning
confidence: 99%
“…In animals without tissue injury, high-frequency TENS produces analgesia as measured by the tail flick test 31 and reduces dorsal horn neuron responses to noxious stimuli. 6,9 In an animal model of nerve injury, high-frequency TENS reduces hyperalgesia when applied ipsilaterally on the skin of L1-L6 segments if the treatment was started within the first day after surgery but not if given after development of hyperalgesia. 29 Both high-and low-frequency TENS reduce mechanical and heat hyperalgesia in animals with joint inflammation, muscle inflammation, or cutaneous inflammation.…”
Section: Discussionmentioning
confidence: 99%